A kind of sound insulation and damping nylon sheet and preparation method thereof

By introducing calcium carbonate-montmorillonite composite material, aminated silica and modified zinc oxide into the acrylic plate, the problems of low sound insulation, low tensile strength and poor flame retardant performance of the acrylic plate are solved, and the sound insulation effect is improved, increasing tensile strength and improving flame retardant performance are achieved.

CN119462997BActive Publication Date: 2025-04-01SHANDONG KELESI NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510047000.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-01
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing acrylic plates have problems such as low sound insulation, low tensile strength and poor flame retardant performance, which affects their actual use.

Method used

Soundproof damped acrylic plates were prepared by introducing calcium carbonate-montmorillonite composite materials on the basis of methyl methacrylate and combining the combination of aminolated silica and modified zinc oxide.

Benefits of technology

It effectively improves the sound insulation volume of the sound insulation damping acrylic plate, increases its tensile strength, and obtains good flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and specifically relates to a sound-insulating and damping nylon sheet and a preparation method thereof. The present invention is based on methyl methacrylate, introduces a calcium carbonate-montmorillonite composite material, and uses amino silicon dioxide and modified zinc oxide together to prepare a sound-insulating and damping nylon sheet, which effectively improves the sound insulation, increases the tensile strength, and obtains good flame retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a sound-insulating and damping nylon sheet and a preparation method thereof. Background Art

[0002] Acrylic is a transliteration of the English word Acrylic, also known as organic glass or PMMA (polymethyl methacrylate), which is a common transparent thermoplastic resin; it has the advantages of light weight, low price, and easy molding. The molding methods include casting, injection molding, machining, thermoforming, etc. Injection molding, in particular, can be mass-produced, with a simple process and low cost. It is widely used in instrument parts, automobile lights, optical lenses, etc. However, due to the gap between the surface hardness, heat resistance, and fire resistance of acrylic sheets and ordinary glass, various modification studies such as heat resistance, wear resistance, and flame retardancy have also been conducted on acrylic sheets.

[0003] A Chinese patent (publication number CN114350093A) discloses an acrylic sheet and its preparation method. The acrylic sheet prepared by the invention is made of a high molecular weight acrylic polymer, modified ultrafine glass fiber, and flame retardant composite filler. It has good impact resistance, hardness, and is flame retardant and antibacterial. The modified ultrafine glass fiber used has greatly improved its strength from the morphology and surface modification. In addition, the glass fiber and acrylic polymer are closely cross-linked by grafting tetramethyl divinyl disiloxane and 1-vinyl imidazole. At the same time, the imidazole group can play a good bactericidal role, giving the acrylic sheet additional antibacterial properties. However, the patent does not solve the problems of low sound insulation, low tensile strength, and poor flame retardant properties of acrylic sheets in the prior art, which seriously affects its actual use.

[0004] Therefore, how to screen suitable components and perform corresponding modification treatments to prepare sound-insulating and damping acrylic sheets, improve sound insulation, increase tensile strength, and obtain good flame retardant properties has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a sound-insulating acrylic board and a preparation method thereof, aiming to solve the problems of low sound insulation, low tensile strength and poor flame retardant properties existing in the existing acrylic board.

[0006] The present invention prepares a sound-insulating and damping nylon sheet based on methyl methacrylate by introducing a calcium carbonate-montmorillonite composite material and using amino silicon dioxide and modified zinc oxide together, thereby effectively improving the sound insulation and tensile strength and obtaining good flame retardant properties.

[0007] The technical solution of the present invention is as follows:

[0008] A first aspect of the present invention provides a method for preparing a sound-insulating nylon sheet, comprising the following steps:

[0009] Step S1: in parts by weight, 6-10 parts of dodecyl phosphate, 10-16 parts of calcium carbonate and 180-200 parts of deionized water are mixed uniformly, and the mixture is shaken at a constant temperature of 70-80° C. for 30-40 minutes, filtered, dried and ground to obtain phosphorus-containing calcium carbonate; 80-90 parts of montmorillonite are added to 200-300 parts of anhydrous ethanol and ultrasonically dispersed for 30-40 minutes, and then 80-100 parts of methyltrichlorosilane are added, and the mixture is stirred at 26-30° C. for 18-20 hours to obtain chlorosilane-modified montmorillonite; 80-90 parts of the chlorosilane-modified .... ~300 parts of tetrahydrofuran, ultrasonically dispersed for 40~50 minutes, then added 26~30 parts of 4-hydroxyphthalic anhydride and 6~8 parts of sodium hydride at 2~4°C, reacted at 24~30°C for 26~30 hours to obtain modified montmorillonite; 20~30 parts of phosphorus-containing calcium carbonate were added to 400~500 parts of deionized water, ultrasonically dispersed for 40~60 minutes, then 40~50 parts of modified montmorillonite, 2~4 parts of sodium dodecylbenzene sulfonate and 4~8 parts of ethylenediaminetetraacetic acid were added, ultrasonically dispersed for 60~90 minutes, filtered, dried, and ground to obtain a calcium carbonate-montmorillonite composite material;

[0010] Step S2: by weight, 110-120 parts of methyl methacrylate and 0.4-0.6 parts of dibenzoyl peroxide are mixed and stirred for 20-30 minutes, then reacted at 86-90° C. for 50-60 minutes, and cooled to room temperature to obtain a prepolymer;

[0011] Step S3: In parts by weight, 8 to 12 parts of calcium carbonate-montmorillonite composite material, 4 to 8 parts of silicon dioxide, 2 to 6 parts of zinc oxide and 0.6 to 0.8 parts of defoaming agent are added to 110 to 120 parts of the prepolymer and stirred for 30 to 40 minutes, and then transferred to a mold for heating polymerization reaction. After the heating polymerization reaction is completed, it is cooled to room temperature, demolded, and polished to obtain a sound insulation and damping Nylon board.

[0012] As a preferred technical solution of the present invention, the particle size of the calcium carbonate is 80~120nm.

[0013] The calcium carbonate in the calcium carbonate-montmorillonite composite material can change the internal microstructure of the acrylic board through nano-level dispersion, so that the sound waves encounter more interfaces and obstacles during the propagation process, thereby increasing the scattering and reflection of the sound waves; the addition of montmorillonite can enhance the damping characteristics of the acrylic board. By increasing the damping, the sound waves consume more energy during the propagation process, thereby reducing the intensity of the sound. The combined effect improves the sound insulation of the acrylic board.

[0014] As a preferred technical solution of the present invention, the silicon dioxide is amino silicon dioxide; the preparation method of the amino silicon dioxide comprises: adding 8 to 12 parts of silicon dioxide to 260 to 300 parts of deionized water by weight, ultrasonically dispersing at room temperature for 30 to 40 minutes, then adding 2 to 6 parts of 3-aminopropyltriethoxysilane, and adjusting the pH to 7.2 to 7.6 for stirring reaction, centrifuging after the stirring reaction is completed, washing the solid obtained by centrifugation with deionized water three times, and vacuum drying to obtain amino silicon dioxide.

[0015] As a preferred technical solution of the present invention, the stirring reaction conditions include: a stirring speed of 100-200 r / min, a temperature of 70-74° C., and a time of 10-12 h.

[0016] Aminated silica can be evenly dispersed in the molecular chains of the polymer matrix and act as a stress concentration point when subjected to external force, dispersing the stress originally concentrated in certain areas to a larger range, preventing material breakage caused by excessive local stress, thereby improving the overall tensile strength of the acrylic sheet.

[0017] As a preferred technical solution of the present invention, the zinc oxide is modified zinc oxide; the preparation method of the modified zinc oxide comprises: in parts by weight, 80-100 parts of zinc oxide and 20-30 parts of borate are uniformly mixed, ball milled at a rotation speed of 200-300 rpm for 4-6 hours, then dispersed in 400-500 parts of acetone and stirred for 6-8 hours, and vacuum dried at 80-90° C. for 20-24 hours to obtain modified zinc oxide.

[0018] As a preferred technical solution of the present invention, the particle size of the zinc oxide is 100~500nm.

[0019] As a preferred technical solution of the present invention, the borate is sodium borate and potassium borate; the mass ratio of the sodium borate to the potassium borate is (1~2):1.

[0020] Modified zinc oxide contains borates, which melt under high temperature conditions and form a dense glass-like covering layer, which can effectively isolate oxygen and heat, prevent the flame from spreading further, and reduce the release of combustible gases, thereby improving the oxygen index of the acrylic sheet.

[0021] As a preferred technical solution of the present invention, the defoaming agent is selected from any one of dimethylpolysiloxane, dimethyl silicone oil, and oleyl alcohol, or a combination of at least two of them.

[0022] As a preferred technical solution of the present invention, the conditions of the heating polymerization reaction include: reacting at 50-60°C for 4-6h, reacting at 70-80°C for 60-70min, and reacting at 100-110°C for 20-30min.

[0023] The second aspect of the present invention provides a sound-insulating and damping Nylon sheet prepared by the method described in the first aspect.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The calcium carbonate-montmorillonite composite material of the present invention is modified by 4-hydroxyphthalic anhydride to introduce active group carboxyl, which can not only combine with the amino group of amino-modified silica, but also react with the borate in modified zinc oxide to form borate ester, thereby constructing a three-dimensional network to ensure dimensional stability and improve the tensile strength of the acrylic board. At the same time, the layered structure of montmorillonite in the three-dimensional network can capture and absorb sound wave energy and enhance the sound insulation effect.

[0026] (2) The calcium carbonate-montmorillonite composite material of the present invention introduces phosphorus-based groups through phosphate modification. The phosphorus-based groups will generate phosphaphenanthrene groups in the gas phase, which can capture free radicals of gas phase cracking gases to form a stable structure and play a free radical quenching role; the silicon element in the amino silicon dioxide can promote the formation of a stable carbon layer on the surface of the material, reduce the generation of volatile combustibles, and thus inhibit the spread of flames; the borate in the modified zinc oxide will melt under high temperature conditions and form a dense glass-like covering layer, which can effectively isolate oxygen and heat through the covering; through the synergistic effect of multiple elements of phosphorus-silicon-boron, the flame retardant properties of the acrylic board are improved.

[0027] (3) The calcium carbonate in the calcium carbonate-montmorillonite composite material of the present invention can change the internal microstructure of the acrylic board through nano-level dispersion, so that the sound waves encounter more interfaces and obstacles during the propagation process, thereby increasing the scattering and reflection of the sound waves; the addition of montmorillonite can enhance the damping characteristics of the acrylic board. By increasing the damping, the sound waves consume more energy during the propagation process, thereby reducing the intensity of the sound. The combined effect improves the sound insulation of the acrylic board.

[0028] (4) The amino silica of the present invention can be evenly dispersed in the molecular chains of the polymer matrix and act as a stress concentration point when subjected to external force, dispersing the stress originally concentrated in certain areas to a larger range, preventing material breakage caused by excessive local stress, thereby improving the overall tensile strength of the acrylic sheet.

[0029] (5) The modified zinc oxide of the present invention contains borate, which melts under high temperature conditions and forms a dense glassy covering layer, which can effectively isolate oxygen and heat, prevent the flame from spreading further, and reduce the release of combustible gas, thereby improving the oxygen index of the acrylic sheet. DETAILED DESCRIPTION

[0030] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0031] The sources of some components in the embodiments and comparative examples are as follows:

[0032] Methyl methacrylate, CAS No. 80-62-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0033] Calcium carbonate I, product number GF-100, particle size 100 nm, purchased from Jiangxi Bairui Calcium Carbonate Co., Ltd.;

[0034] Calcium carbonate II, product number ACC-818, particle size 2 μm, purchased from Xinrong (Lianzhou) Powder Technology Co., Ltd.;

[0035] Calcium carbonate III, product number C886288, particle size 50 nm, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0036] Montmorillonite, model WSG-PN06, was purchased from Shanghai Wanzhao Fine Chemical Co., Ltd.;

[0037] Silicon dioxide, catalog number zkky7767653-0135, was purchased from Beijing Zhongke Keyou Technology Co., Ltd.;

[0038] Zinc oxide I, product number Z112848, particle size 100 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0039] Zinc oxide II, product number Z112847, particle size 25 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0040] Zinc oxide III, product number Z431819, particle size 4 μm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0041] Dibenzoyl peroxide, CAS No. 94-36-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0042] Dimethylpolysiloxane, CAS No. 8050-81-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0043] Dimethyl silicone oil, CAS No. 63148-62-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0044] Oleyl alcohol, CAS No. 143-28-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0045] Sodium dodecylbenzenesulfonate, CAS No. 25155-30-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0046] Ethylenediaminetetraacetic acid, CAS No. 60-00-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0047] Dodecyl phosphate, CAS No. 2627-35-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0048] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0049] Methyltrichlorosilane, CAS No. 75-79-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0050] Tetrahydrofuran, CAS No. 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0051] 4-Hydroxyphthalic anhydride, CAS No. 27550-59-0, purchased from Jinde Chemical Technology (Shanghai) Co., Ltd.;

[0052] Sodium hydride, CAS No. 7646-69-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0053] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0054] Sodium borate, CAS No. 1330-43-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0055] Potassium borate, CAS No. 12045-78-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0056] Acetone, CAS No. 67-64-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0057] Example 1

[0058] This embodiment provides a method for preparing a sound-insulating nylon sheet, comprising the following steps:

[0059] Preparation of amino silica: In parts by weight, 12 parts of silica were added to 300 parts of deionized water, ultrasonically dispersed at room temperature for 40 minutes, and then 6 parts of 3-aminopropyltriethoxysilane were added, and the pH was adjusted to 7.6 for stirring reaction (stirring speed of 200 r / min, temperature of 74°C, time of 10 hours). After the stirring reaction was completed, centrifugation was performed, and the solid obtained by centrifugation was washed three times with deionized water and vacuum dried to obtain amino silica.

[0060] Preparation of modified zinc oxide: In parts by weight, 100 parts of zinc oxide I (particle size 100 nm) and 30 parts of borate (20 parts of sodium borate and 10 parts of potassium borate) were mixed evenly, ball-milled at a rotation speed of 300 rpm for 6 hours, then dispersed in 500 parts of acetone and stirred for 8 hours, and vacuum dried at 90°C for 20 hours to obtain modified zinc oxide.

[0061] Step S1: In parts by weight, 10 parts of dodecyl phosphate, 16 parts of calcium carbonate I (particle size of 100 nm) and 200 parts of deionized water are mixed evenly, and the mixture is shaken at a constant temperature of 80°C for 30 minutes, filtered, dried and ground to obtain phosphorus-containing calcium carbonate; 90 parts of montmorillonite are added to 300 parts of anhydrous ethanol and ultrasonically dispersed for 40 minutes, and then 100 parts of methyltrichlorosilane are added and stirred at 30°C for 18 hours to obtain chlorosilane-modified montmorillonite; 90 parts of the chlorosilane-modified montmorillonite are added to 300 parts of anhydrous ethanol and ultrasonically dispersed for 40 minutes, and then 100 parts of methyltrichlorosilane are added and stirred at 30°C for 18 hours to obtain chlorosilane-modified montmorillonite. The clay was added into 300 parts of tetrahydrofuran and ultrasonically dispersed for 50 minutes, then 30 parts of 4-hydroxyphthalic anhydride and 8 parts of sodium hydride were added at 4°C, and the mixture was reacted at 30°C for 26 hours to obtain modified montmorillonite; 30 parts of phosphorus-containing calcium carbonate were added into 500 parts of deionized water and ultrasonically dispersed for 60 minutes, then 50 parts of modified montmorillonite, 4 parts of sodium dodecylbenzene sulfonate and 8 parts of ethylenediaminetetraacetic acid were added and ultrasonically dispersed for 90 minutes, filtered, dried and ground to obtain a calcium carbonate-montmorillonite composite material;

[0062] Step S2: by weight, 120 parts of methyl methacrylate and 0.6 parts of dibenzoyl peroxide were mixed and stirred for 30 minutes, then reacted at 90° C. for 50 minutes, and cooled to room temperature to obtain a prepolymer;

[0063] Step S3: In parts by weight, 12 parts of calcium carbonate-montmorillonite composite material, 8 parts of amino silica, 6 parts of modified zinc oxide and 0.8 parts of defoaming agent dimethyl polysiloxane are added to 120 parts of the prepolymer and stirred for 40 minutes, and then transferred to a mold for a heating polymerization reaction (reacting at 60°C for 4 hours, reacting at 80°C for 60 minutes, and reacting at 110°C for 20 minutes). After the heating polymerization reaction is completed, it is cooled to room temperature, demolded, and polished to obtain a sound insulation and damping acrylic board.

[0064] Example 2

[0065] This embodiment provides a method for preparing a sound-insulating nylon sheet, comprising the following steps:

[0066] Preparation of amino silica: In parts by weight, 8 parts of silica were added to 260 parts of deionized water, ultrasonically dispersed at room temperature for 30 minutes, and then 2 parts of 3-aminopropyltriethoxysilane were added, and the pH was adjusted to 7.2 for stirring reaction (stirring speed of 100 r / min, temperature of 70°C, time of 12 hours). After the stirring reaction was completed, centrifugation was performed, and the solid obtained by centrifugation was washed three times with deionized water and vacuum dried to obtain amino silica.

[0067] Preparation of modified zinc oxide: In parts by weight, 80 parts of zinc oxide I (particle size 100 nm) and 20 parts of borates (10 parts of sodium borate and 10 parts of potassium borate) were mixed evenly, ball-milled at a rotation speed of 200 rpm for 6 hours, then dispersed in 400 parts of acetone and stirred for 6 hours, and vacuum dried at 80°C for 24 hours to obtain modified zinc oxide.

[0068] Step S1: In parts by weight, 6 parts of dodecyl phosphate, 10 parts of calcium carbonate I (particle size of 100 nm) and 180 parts of deionized water are mixed evenly, and the mixture is shaken at a constant temperature of 70°C for 40 minutes, filtered, dried and ground to obtain phosphorus-containing calcium carbonate; 80 parts of montmorillonite are added to 200 parts of anhydrous ethanol and ultrasonically dispersed for 30 minutes, and then 80 parts of methyltrichlorosilane are added and stirred at 26°C for 18 hours to obtain chlorosilane-modified montmorillonite; 80 parts of the chlorosilane-modified montmorillonite are added to 200 parts of anhydrous ethanol and ultrasonically dispersed for 30 minutes, and then 80 parts of methyltrichlorosilane are added and stirred at 26°C for 18 hours to obtain chlorosilane-modified montmorillonite. Add to 200 parts of tetrahydrofuran and ultrasonically disperse for 40 minutes, then add 26 parts of 4-hydroxyphthalic anhydride and 6 parts of sodium hydride at 2°C, react at 24°C for 30 hours to obtain modified montmorillonite; add 20 parts of phosphorus-containing calcium carbonate to 400 parts of deionized water and ultrasonically disperse for 40 minutes, then add 40 parts of modified montmorillonite, 2 parts of sodium dodecylbenzene sulfonate and 4 parts of ethylenediaminetetraacetic acid and ultrasonically disperse for 60 minutes, filter, dry and grind to obtain a calcium carbonate-montmorillonite composite material;

[0069] Step S2: by weight, 110 parts of methyl methacrylate and 0.4 parts of dibenzoyl peroxide were mixed and stirred for 20 minutes, then reacted at 86° C. for 60 minutes, and cooled to room temperature to obtain a prepolymer;

[0070] Step S3: In parts by weight, 8 parts of calcium carbonate-montmorillonite composite material, 4 parts of amino silica, 2 parts of modified zinc oxide and 0.6 parts of defoaming agent dimethyl silicone oil are added to 110 parts of the prepolymer and stirred for 30 minutes, and then transferred to a mold for heating polymerization reaction (reacting at 50°C for 6 hours, reacting at 70°C for 70 minutes, and reacting at 100°C for 30 minutes). After the heating polymerization reaction is completed, it is cooled to room temperature, demolded, and polished to obtain a sound insulation and damping Nylon board.

[0071] Example 3

[0072] This embodiment provides a method for preparing a sound-insulating nylon sheet, comprising the following steps:

[0073] Preparation of amino silica: In parts by weight, 10 parts of silica were added to 280 parts of deionized water, ultrasonically dispersed at room temperature for 35 minutes, then 4 parts of 3-aminopropyltriethoxysilane were added, and the pH was adjusted to 7.4 for stirring reaction (stirring speed of 150 r / min, temperature of 72°C, time of 11 hours), and after the stirring reaction was completed, centrifugation was performed, and the solid obtained by centrifugation was washed three times with deionized water and vacuum dried to obtain amino silica.

[0074] Preparation of modified zinc oxide: In parts by weight, 90 parts of zinc oxide I (particle size 100 nm) and 25 parts of borates (15 parts of sodium borate and 10 parts of potassium borate) were mixed evenly, ball-milled at a rotation speed of 250 rpm for 5 hours, then dispersed in 450 parts of acetone and stirred for 7 hours, and vacuum dried at 85°C for 22 hours to obtain modified zinc oxide.

[0075] Step S1: In parts by weight, 8 parts of dodecyl phosphate, 12 parts of calcium carbonate I (particle size of 100 nm) and 190 parts of deionized water are mixed evenly, and the mixture is shaken at a constant temperature of 75°C for 35 minutes, filtered, dried and ground to obtain phosphorus-containing calcium carbonate; 85 parts of montmorillonite are added to 250 parts of anhydrous ethanol and ultrasonically dispersed for 35 minutes, and then 90 parts of methyltrichlorosilane are added and stirred at 28°C for 19 hours to obtain chlorosilane-modified montmorillonite; 85 parts of the chlorosilane-modified montmorillonite are added to 250 parts of anhydrous ethanol and ultrasonically dispersed for 35 minutes, and then 90 parts of methyltrichlorosilane are added and stirred at 28°C for 19 hours to obtain chlorosilane-modified montmorillonite. Add to 250 parts of tetrahydrofuran and ultrasonically disperse for 45 minutes, then add 28 parts of 4-hydroxyphthalic anhydride and 7 parts of sodium hydride at 3°C, react at 28°C for 28 hours to obtain modified montmorillonite; add 25 parts of phosphorus-containing calcium carbonate to 450 parts of deionized water and ultrasonically disperse for 50 minutes, then add 45 parts of modified montmorillonite, 3 parts of sodium dodecylbenzene sulfonate and 6 parts of ethylenediaminetetraacetic acid and ultrasonically disperse for 80 minutes, filter, dry and grind to obtain a calcium carbonate-montmorillonite composite material;

[0076] Step S2: by weight, 115 parts of methyl methacrylate and 0.5 parts of dibenzoyl peroxide were mixed and stirred for 25 minutes, then reacted at 88° C. for 55 minutes, and cooled to room temperature to obtain a prepolymer;

[0077] Step S3: In parts by weight, 10 parts of calcium carbonate-montmorillonite composite material, 6 parts of amino silica, 4 parts of modified zinc oxide and 0.7 parts of defoaming agent oleyl alcohol are added to 115 parts of the prepolymer and stirred for 35 minutes, and then transferred to a mold for a heating polymerization reaction (reacting at 55°C for 5 hours, reacting at 75°C for 65 minutes, and reacting at 105°C for 25 minutes). After the heating polymerization reaction is completed, it is cooled to room temperature, demolded, and polished to obtain a sound-insulating and damping acrylic board.

[0078] Comparative Example 1

[0079] This comparative example provides a method for preparing an acrylic board, which differs from Example 1 in that calcium carbonate I is used instead of the calcium carbonate-montmorillonite composite material.

[0080] Comparative Example 2

[0081] This comparative example provides a method for preparing an acrylic board, which is different from Example 1 in that calcium carbonate II is used instead of calcium carbonate I to prepare the calcium carbonate-montmorillonite composite material.

[0082] Comparative Example 3

[0083] This comparative example provides a method for preparing an acrylic board, which is different from Example 1 in that calcium carbonate III is used instead of calcium carbonate I to prepare the calcium carbonate-montmorillonite composite material.

[0084] Comparative Example 4

[0085] This comparative example provides a method for preparing an acrylic plate, which differs from Example 1 in that commercially available silicon dioxide is used instead of amino silicon dioxide.

[0086] Comparative Example 5

[0087] This comparative example provides a method for preparing an acrylic plate, which differs from Example 1 in that zinc oxide I is used instead of modified zinc oxide.

[0088] Comparative Example 6

[0089] This comparative example provides a method for preparing an acrylic plate, which is different from Example 1 in that zinc oxide II is used instead of zinc oxide I to prepare modified zinc oxide.

[0090] Comparative Example 7

[0091] This comparative example provides a method for preparing an acrylic plate, which is different from Example 1 in that zinc oxide III is used instead of zinc oxide I to prepare the modified zinc oxide.

[0092] The performance of the acrylic sheets provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0093] (1) Sound insulation test: The test shall be conducted in accordance with the requirements of GB / T 19889.3-2005 Acoustic sound insulation measurement of buildings and building elements Part 3: Laboratory measurement of airborne sound insulation of building elements.

[0094] (2) Tensile strength test: Test according to the requirements of GB / T 1040.1-2018 Determination of tensile properties of plastics Part 1: General.

[0095] (3) Oxygen index test: The test shall be conducted in accordance with the requirements of GB / T 2406.2-2009 Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test.

[0096] The above performance test data is shown in Table 1.

[0097] Table 1 Performance test results

[0098]

[0099] From the above content, it can be seen that the present invention, on the basis of methyl methacrylate, introduces a calcium carbonate-montmorillonite composite material, and uses amino silica and modified zinc oxide together to prepare a sound-insulating acrylic board (Example 1 to Example 3). The sound insulation (50dB) of the acrylic board is 20.9~21.6dB, the tensile strength is 94.1~94.8MPa, and the oxygen index is 34.7~35.4%.

[0100] Compared with Example 1, calcium carbonate I was used to replace the calcium carbonate-montmorillonite composite material, and the sound insulation was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 1); Compared with Example 1, calcium carbonate II was used to replace calcium carbonate I to prepare the calcium carbonate-montmorillonite composite material. Since the particle size of calcium carbonate II was too large, the modification effect was not good, the sound insulation was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 2); Compared with Example 1, calcium carbonate III was used to replace calcium carbonate I to prepare the calcium carbonate-montmorillonite composite material. Since the particle size of calcium carbonate III was too small, the modification effect was not good, the sound insulation was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 3); Compared with Example 1, commercially available silica was used to replace calcium carbonate I. Compared with Example 1, zinc oxide I was used to replace modified zinc oxide, the sound insulation value was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 4); compared with Example 1, zinc oxide I was used to replace modified zinc oxide, the sound insulation value was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 5); compared with Example 1, zinc oxide II was used to replace zinc oxide I for the preparation of modified zinc oxide. Since the particle size of zinc oxide II was too small, the modification effect was not good, the sound insulation value was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 6); compared with Example 1, zinc oxide III was used to replace zinc oxide I for the preparation of modified zinc oxide. Since the particle size of zinc oxide III was too large, the modification effect was not good, the sound insulation value was reduced, the tensile strength was reduced, and the oxygen index was reduced (Comparative Example 7).

[0101] In summary, the present invention, based on methyl methacrylate, introduces a calcium carbonate-montmorillonite composite material, and uses amino silica and modified zinc oxide together to prepare a sound-insulating and damping nylon sheet, which effectively improves the sound insulation and tensile strength, and at the same time obtains good flame retardant properties.

Claims

1. A method for preparing a sound-insulating nylon sheet, characterized in that: The following steps are involved: Step S1: in parts by weight, 6-10 parts of dodecyl phosphate, 10-16 parts of calcium carbonate and 180-200 parts of deionized water are mixed uniformly, and the mixture is shaken at a constant temperature of 70-80° C. for 30-40 minutes, filtered, dried and ground to obtain phosphorus-containing calcium carbonate; 80-90 parts of montmorillonite are added to 200-300 parts of anhydrous ethanol for ultrasonic dispersion for 30-40 minutes, and then 80-100 parts of methyltrichlorosilane are added, and the mixture is stirred at 26-30° C. for 18-20 hours to obtain chlorosilane-modified montmorillonite; 80-90 parts of the chlorosilane-modified montmorillonite are added to 200-300 parts of tetrahydrofuran for ultrasonic dispersion for 40-50 minutes, and then 26-30 parts of 4-hydroxyphthalic anhydride and 6-8 parts of sodium hydride are added at 2-4° C., and the mixture is reacted at 24-30° C. for 26-30 hours to obtain modified montmorillonite; 20-30 parts of phosphorus-containing calcium carbonate are added to 400-500 parts of deionized water for ultrasonic dispersion for 40-60 minutes, and then 40-50 parts of modified montmorillonite, 2-4 parts of sodium dodecylbenzene sulfonate and 4-8 parts of ethylenediaminetetraacetic acid are added for ultrasonic dispersion for 60-90 minutes, filtered, dried and ground to obtain a calcium carbonate-montmorillonite composite material; Step S2: by weight, 110-120 parts of methyl methacrylate and 0.4-0.6 parts of dibenzoyl peroxide are mixed and stirred for 20-30 minutes, then reacted at 86-90° C. for 50-60 minutes, and cooled to room temperature to obtain a prepolymer; Step S3: adding 8 to 12 parts of calcium carbonate-montmorillonite composite material, 4 to 8 parts of amino silica, 2 to 6 parts of modified zinc oxide and 0.6 to 0.8 parts of defoaming agent to 110 to 120 parts of the prepolymer by weight, stirring for 30 to 40 minutes, and then transferring to a mold for heating polymerization reaction, cooling to room temperature after the heating polymerization reaction, demolding, and polishing to obtain a sound insulation and damping Nylon sheet; The particle size of the calcium carbonate is 80-120 nm; The preparation method of the amino silicon dioxide comprises: adding 8 to 12 parts of silicon dioxide to 260 to 300 parts of deionized water by weight, ultrasonically dispersing at room temperature for 30 to 40 minutes, then adding 2 to 6 parts of 3-aminopropyltriethoxysilane, adjusting the pH to 7.2 to 7.6, stirring and reacting, centrifuging after the stirring reaction is completed, washing the solid obtained by centrifugation with deionized water three times, and vacuum drying to obtain the amino silicon dioxide; The preparation method of the modified zinc oxide comprises: mixing 80-100 parts of zinc oxide and 20-30 parts of borate uniformly by weight, ball milling for 4-6 hours at a rotation speed of 200-300 rpm, then dispersing into 400-500 parts of acetone and stirring for 6-8 hours, and vacuum drying at 80-90° C. for 20-24 hours to obtain the modified zinc oxide.

2. The method for preparing a sound-insulating acrylic sheet according to claim 1, characterized in that: The stirring reaction conditions include: stirring speed of 100-200 r / min, temperature of 70-74° C., and time of 10-12 h.

3. The method for preparing a sound-insulating acrylic sheet according to claim 1, characterized in that: The particle size of the zinc oxide is 100-500 nm.

4. The method for preparing a sound-insulating nylon sheet according to claim 1, characterized in that: The borate is sodium borate and potassium borate; the mass ratio of the sodium borate to potassium borate is (1-2):

1.

5. The method for preparing a sound-insulating nylon sheet according to claim 1, characterized in that: The defoaming agent is selected from any one of dimethylpolysiloxane, dimethyl silicone oil, and oleyl alcohol, or a combination of at least two of them.

6. The method for preparing a sound-insulating nylon sheet according to claim 1, characterized in that: The conditions of the thermal polymerization reaction include: reacting at 50-60° C. for 4-6 hours, reacting at 70-80° C. for 60-70 minutes, and reacting at 100-110° C. for 20-30 minutes.

7. A sound-insulating nylon sheet, characterized in that: Prepared according to the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Acrylic plate and preparation method thereof

    CN114350093A

  • Polycarboxyl modified montmorillonite in-situ polymerization nylon 6 composite material and preparation method thereof

    CN114262514A

  • High-strength impact-resistant acrylic plate and processing technology thereof

    CN115322418A

  • Modification method of nano calcium carbonate for silicone sealant

    CN118652566A

  • Multiwall sheet and methods for making and using the same

    US20130052429A1